Pattern and influencing factors of breastfeeding of working mothers in several areas in Jakarta - Rifan Fauzie; Rulina Suradi; Sri Rezeki S. Hadinegoro (Paediatrica Indonesiana, 2007)
Background Breast milk contains many essential nutrition factorsbest for babies. The 1997 Indonesian Health Demography foundthat the proportion of exclusive breastfeeding was still low (52%)and increased to 55.1% in 2002. Due to increasing number ofworking mothers, promoting breast feeding among them should beperformed properly. There are no data on exclusive breastfeedingrate and pattern among working mothers in Indonesia.Objective To describe exclusive breastfeeding rate and patternamong working mothers in several areas in Jakarta and the influ-encing factors.Methods A descriptive study using a questionnaire was conductedfrom October 2005 to February 2006. Subjects were workingmothers who had 6 to 12 month old baby and breastfed and thebaby had no congenital or chronic disease.Results Among 290 mothers interviewed, 40% worked at banksor insurance business, 34% were private employees, 25% medicalstaffs, and 2% were teachers. Almost 80% have exclusivelybreastfed for less than 4 months, 17% for 4 months, and only 4%for 6 months. Maternal leave, family support, mothers’ knowl-edge, facilities at workplace, media influences, and working hoursseemed to have no relations to breastfeeding rate. There were122 (42%) mothers who had good knowledge about physiologyof lactation, 155 of them (53%) had fair knowledge, and only45% of them had poor knowledge.Conclusions The proportion of working mothers in several areasin Jakarta who have exclusively breastfed for 4 months is 17%, andonly 4% of subjects do exclusive breastfeeding for 6 months. Mostsubjects have a good to fair knowledge about the physiology oflactation but it does not seem to influence the decision to exclu-sively breastfed their babies.